Combined Effect of Organic Manure and Potassium on Growth and Yield of Onion cv. Bari piaz-I - Barman, HK; Siddiqui, MN; Siddique, MA; Roni, MS; Nuruzzaman, M (International Journal of Agricultural Research, Innovation and Technology, 2013)
An experiment was conducted to find out the combined effect of cowdung and potassium on the growth and yield of onion cv. BARI piaz-I at Horticulture Farm, Bangladesh Agricultural University, Mymensingh during the period from December 2010 to March 2011. The experiment was laid out in a randomized complete block design with three replications. The two factors experiment had four levels of cowdung, viz., 0, 5, 10 and 20 tons ha-1 and four levels of potassium, viz. 0, 50, 150 and 250 kg K ha-1. Doses of cowdung and potassium showed significant variation in respect of all the parameters studied. The combination of 10 tons cowdung and 250 kg K ha-1 gave the tallest plant (46.60 cm), the highest number of leaves plant-1 (6.40), the highest length of bulb (3.27 cm), the highest diameter of bulb (4.83 cm), individual weight of bulb (51.23 g), dry matter content (12.66%) and yield of bulb ha-1 (12.83 tons); whereas the control treatment gave the shortest plant (38.15 cm), lowest number of leaves plant-1 (5.68), diameter of bulb (3.41), individual weight of bulb (35.65g) and gave lowest bulb yield ha-1 (9.16 tons). Int. J. Agril. Res. Innov. & Tech. 3 (1): 47-51, June, 2013 DOI: http://dx.doi.org/10.3329/ijarit.v3i1.16092